Immunological study on some of Psoriatic Iraqi PatientsTreated with Etanercept - Abd-Alkhaliq, Ghufran Qasem; Abd, Wisal Salman (International Journal of Psychosocial Rehabilitation, 2020)
The present study is accomplished on (60) patients and (30) healthy individual. Serum levels of (Interleukin 17A (IL17A), Interleukin 17AR (IL17AR)and anticitrullinated protein antibody(ANTI-CCP) is estimated using Enzyme Linked Immunosorbent Assay (ELISA) technique and RF by latex test. Our results were high starting with IL17A mean value before treatment (967.24±784.1), IL17AR (818.62±647.33),ANTI-CCP (33.96±51.82) and with P value of (